2020
DOI: 10.1039/d0bm00361a
|View full text |Cite
|
Sign up to set email alerts
|

3D printed porous titanium cages filled with simvastatin hydrogel promotes bone ingrowth and spinal fusion in rhesus macaques

Abstract: Sustainable release of simvastatin from poloxamer 407 hydrogel in 3D-printed porous Ti6Al4V for spinal fusion in rhesus macaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…The VPA hydrogel was synthesized as described [ 20 ]. Briefly, 200 μl of poloxamer 407 hydrogel (BASF, Ludwigshafen, Germany) (1/4 volume ratio) was mixed with 50 μg of valproic acid and 0.01 M phosphate-buffered saline (PBS) (pH 7.4, at 4 °C).…”
Section: Methodsmentioning
confidence: 99%
“…The VPA hydrogel was synthesized as described [ 20 ]. Briefly, 200 μl of poloxamer 407 hydrogel (BASF, Ludwigshafen, Germany) (1/4 volume ratio) was mixed with 50 μg of valproic acid and 0.01 M phosphate-buffered saline (PBS) (pH 7.4, at 4 °C).…”
Section: Methodsmentioning
confidence: 99%
“…Our large animal study showed that 0.5 and 1 mg injections of simvastatin in minipig vertebrae were effective to enhance implant fixation and improve bone quality 8,9 . Our previous data showed that 3D‐printed porous cages with 0.5 mg simvastatin in hydrogel can promote bone ingrowth and spinal fusion in adult male rhesus macaques 10 . The possible overdose in this study may also explain the phenomenon that we did not find any difference between the SIM‐C 0.5 mg and SIM‐BPC 0.5 mg group in the osteoporosis model.…”
Section: Discussionmentioning
confidence: 74%
“…Local delivery of simvastatin is another option that can be used. Our previous studies have shown that locally applied statins with sustained release can improve the quality of osteoporotic bone, promote defect healing, or enhance pedicle‐screw fixation in animals, from rats 6 and rabbits, 7 to minipigs 8,9 and rhesus macaques 10 …”
Section: Introductionmentioning
confidence: 99%
“…When hydrogel is used as a drug carrier, it disseminates drug molecules into surrounding tissues or cells through interconnected pores ( Chyzy and Plonska-Brzezinska, 2020 ). For instance, Zhang W et al (2020) developed a poloxamer 407 hydrogel loaded with simvastatin for filling porous 3D-printed titanium alloy intervertebral cages that achieved stable drug release and significantly promoted bone growth. Furthermore, the strategy of promoting bone regeneration through stem cell transplantation has become an important research topic to repair bone defects and promote bone integration.…”
Section: Surface Modification Technologymentioning
confidence: 99%